Research progress on the allergic mechanism, molecular properties, and immune cross-reactivity of the egg allergen Gal d 5 - Jiaqi, Wei; Yanjun, Cong (Frontiers in Nutrition, 2023)
Eggs and their products are commonly consumed in food products worldwide, and in addition to dietary consumption, egg components are widely used in the food industry for their antimicrobial, cooking, and other functional properties. Globally, eggs are the second most common food allergen after milk. However, current research on egg allergy primarily focuses on egg white allergens, while little research has been done on egg yolk allergens. Therefore, summarizing and analyzing the important allergen α-livetin in egg yolk is significant in elucidating the mechanism of egg allergy and exploring effective desensitization methods. This paper discusses the incidence, underlying mechanism, and clinical symptoms of egg allergy. This article provides a comprehensive summary and analysis of the current research status concerning the molecular structural properties, epitopes, and immune cross-reactivity of the egg yolk allergen, Gal d 5. Additionally, it examines the effects of various processing methods on egg allergens. The article also offers suggestions and outlines potential future research directions and ideas in this field.